Correlation between Glycated Haemoglobin Level, Cardiac Function, and Prognosis in Patients with Diabetes Mellitus Combined with Myocardial Infarction. (23rd September 2022) - Zeng, Guangwei; An, Huixian; Li, Wei; Fang, Dong; Sun, Mengna; Zheng, Qiangsun
Abstract : Objective . This study was to investigate the correlation between glycated haemoglobin (HbA1c) level, cardiac function, and prognosis in patients with diabetes mellitus combined with myocardial infarction. Methods . Ninety-three patients with type 2 diabetes mellitus combined with acute myocardial infarction who were hospitalized and treated in our hospital from January 2021 to June 2021 were recruited for prospective analysis and equally divided into group A (HbA 1 c < 6.5 % ), group B (6.5 % ≤ HbA 1 c ≤ 8.5 % ), and group C (HbA 1 c > 8.5 % ) using the random number table method, with 31 patients in each group. General data of patients were collected on admission and blood glucose and cardiac function indexes were measured; the incidence of myocardial infarction and death during the follow-up period was recorded at 6 months after discharge. Results . There was a significant difference in blood glucose (FBG) and HbA1c levels at fasting between the three groups (P < 0.05 ). There were statistically significant differences in plasma levels of N-terminal probrain natriuretic peptide (NT-proBNP) and uric acid (UA), left ventricular end diastolic diameter (LVEDD), left ventricular end systolic volume (LVESV), left ventricular ejection fraction (LVEF), and cardiac function classification of the New York Heart Association (NYHA) among the three groups (P < 0.05 ). By statistical analysis, the HbA1c level was positively correlated with FBG, NT-proBNP, UA, LVEDD, LVESD, and NYHA grades but negatively correlated with LVEF (P < 0.05 ). The incidence rate of myocardial infarction and mortality was significantly higher in group C than in groups A and B (P < 0.05 ). Conclusion . HbA1c level in patients with diabetes mellitus combined with myocardial infarction is closely related to the degree of cardiac function damage. Glycated haemoglobin levels are associated with the development of cardiac insufficiency in patients with acute myocardial infarction; glycated haemoglobin is also an independent predictor of major adverse cardiovascular events. Reasonable and effective blood glucose control is of great significance to the prognosis of patients.